Implementation and performance analysis of AODV-PSO with AODV-GA and AODV-ABC - ., Kavita; Sahai, Prashant; Mittal, Sonu (International Journal of Engineering and Technology, 2017)
To upgrade the system lifetime fittingly many steering conventions and bunch based calculations are utilized to accomplish the execution need in WSN. From existing examination approaches, advancement of vitality in correspondence turns out to be extremely basic. Some portion of a vitality utilization of every sensor hub has a vital part while imparting among other sensor hubs for expanding lifetime of the WSN. This examination work concentrates on vitality protection in every sensor hub by utilizing AODV convention with PSO, GA and ABC based bunching and group head choice vitality enhancement calculation. AODV gives a course to correspondence while the group head is chosen utilizing PSO, GA, and ABC in view of the separation from the bunch part hub to sink hub and the leftover vitality in that hub. Reproduction comes about demonstrate that the inspiration of this work enhances the lifetime of the system exceptionally.
Keywords: Wireless Sensor Network; Clustering; Routing Protocols.